Pertumbuhan Tunas Pisang Barangan (Musa Acuminata Colla.) akibat Pemberian Benzyl Amino Purin dan Arang Aktif secara In Vitro. - Mulia Saputri; Marai Rahmawati; Elly Kesumawati (Fakultas Pertanian, Universitas Syiah Kuala, 2019)
Pertumbuhan Tunas Pisang Barangan Akibat Pemberian Benzyl AminoPurin dan Arang Aktif secara In Vitro Accretion of Barangan Banana Shoot Effect of (BAP) and Activated Charcoal Explant by In VitroAbstrak. Banana as a superior product of horticultural crops, has not achieved high productivity and has several obstacles in its multiplication. Tissue culture is one solution to overcome this problem. This study aims to determine the composition of PGRBenzil Amino Purine (BAP) and activated charcoal that are appropriate in the multiplication of barangan banana shoots. This research was conducted at the Tissue Culture Laboratory Faculty of Agriculture Syiah Kuala University, Darussalam Banda Aceh. The design used was a Completely Randomized Design (CRD) with two treatment factors. The first factor is BAP concentration consisting of 3 levels, namely 4 mg/L, 6 mg /L, and 8 mg/L. The second factor is activated charcoal concentration consisting of 3 levels, namely control, 1 g/L and 2 g/L. In this study, from 9 treatment combinations, only 4 treatment combinations were not contaminated. Of the 4 treatment combinations the combination of BAP concentration of 6 mg/L and control (without activated charcoal) showed the fastest shoot growth time of 29 days after multiplication, the most shoot growth was 6 shoots and the average shoot height was 15.9 mm